The Content of Low Density Lipoprotein, High Density Lipoproteins, Cholesterol on Pen Shells (Atrina Pectinata) Fish Catch in Kenjeran Surabaya - Rio Khalif Eldiaz; Agustono Agustono; Kustiawan Tri Pursetyo (Journal of Marine and Coastal Science, 2018)
Pen Shells (A. pectinata) Is one type of a clam that is mostly consumed, Cholesterol levels included in a category high. Although the high cholesterol levels. Shells also contain levels commonly called ldl cholesterol evil . Having shells also levels of hdl, Cholesterol levels total normal in plasma adults is of 120 until 200 mg/dl. Different from its function at the time of cholesterol levels normal, the higher cholesterol levels in the blood, the greater the risk of atherosclerosis also. The purpose of this research is to get information about ldl levels , hdl and cholesterol contained in shells kampak , as well as to determine the shells kampak who most worthy for consumption. Parameter that observed in this research was ldl , hdl , cholesterol .This study using methods descriptive against the difference levels of low density lipopprotein ( ldl ) and high-density lipoproteins ( hdl ) and cholesterol in any bivalve hatchets the results of catch fishermen in kenjeran surabaya. Average levels of ldl on pen shells (A. pictinata) In the meat is 30,990 mg/100g, in the muscle is 28,329 mg/100g and in the Digestive organs is 25,225 mg/100g ; The average levels of hdl on pen shells (A. pictinata) in the meat is 96,772 mg/100g, in the muscle is 87,139 mg/100g and in the Digestive organs is 67,516 mg/100g ; average levels of cholesterol on pen shells (A. pictinata) in the meat is 165,609 mg/100g, in the muscle is 147,382 mg/100g and in the Digestive organs is 114,551 mg/100g. Levels of LDL, HDL and cholesterol Lead to results same that is the most number are located on the meat, then muscle and at least there are on an disgestive organ.